The textual development of the Qumran Community rule - Metso, Sarianna. (Studies on the Texts of the Desert of Judah, 1997)
This volume is concerned with tracing the different stages in the formation of the Qumran Community Rule in the light of the material from Cave 4 that has only recently become available. The first part of this ground-breaking work is devoted to determining the differences between the manuscripts of the Community Rule found in Caves 1, 4 and 5. The second part deals with the relationship between the various versions of the Community Rule. The third part aims at creating an overall picture of the literary development of this document and includes a discussion of the different elements within it as well as a comparison of the parallel passages, which reflect different stages in the redaction of the document.